Trends in intubation rates and durations in ventilated severely injured trauma patients: an analysis from the TraumaRegister DGU®. Issue 1 (December 2016) - Almahmoud, Khalid; Teuben, Michel; Andruszkow, Hagen; Horst, Klemens; Lefering, Rolf; Hildebrand, Frank; Pape, Hans; Pfeifer, Roman
Abstract Background Endotracheal intubation in severely injured patients is known to be a risk factor for systemic complications. We aimed to examine the changes in intubation rates and durations in severely injured trauma patients, and rates of the systemic complications associated with ventilation changes by using a large trauma registry over the period of 13 years. Methods Patient demographics, Injury Severity Score (ISS), ventilation days, ventilation free days (VFD), and prevalence of systemic complications (sepsis and multiple organ failure (MOF)) were obtained from the TraumaRegister DGU® and were compared over the study period. Results During the study period (2002 – 2014), 35, 232 patients were recorded in TraumaRegister DGU®. 72.7 % of patients (n = 25, 629) were intubated, and 27.3 % (n = 9603) of patients did not require mechanical ventilation throughout their hospital stay. The mean age was 48 ± 21 years, mean ISS was 27.9 ± 11.5, mean length of ICU stay was 11.7 ± 13.8 days, mean time on mechanical ventilator was 7.1 ± 11.3 days, and mean ventilation free days (spontaneous respiration) was 19.5 ± 11.9 days. We observed a reduction in the intubation rates (87.5 % in 2002 versus 63.6 % in 2014), and early extubation (10 ventilation days in 2002, and 5.9 days in 2014) over time. Conclusion Our study reveals a reduction in intubation rates and ventilation duration during the observation period. Moreover, we were able to observe decreased incidence of systemic complications such as sepsis over the 13 year study period, while no changes in incidence of MOF were registered. The exact relationship can not be proven in our study. This needs to be addressed in further analysis.